PENGARUH FAKTOR-FAKTOR INTERNAL PERUSAHAAN TERHADAP INCOME SMOOTHING - Etty M. Nasser; Tobia Parulian (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2006)
The objective of this research is to identify the influence of internal factor, such as size, profitability, operating leverage and sectors to the income smoothing practice. And the other objective is to examine the diffrerence between internal factors such as, size, profitability, operating leverage, industrial sectors from companies's income smoothing practice and the other companies's income smoothing practice. This research examine 47 companies listed in Jakarta Stock Exchange and issues ana dited finanacial statement since 2002-2004. The statistical methods used to test the hypothesis are univariate test, such as one-sample mogorov-Smimov test, Mann-Whitney test, Chi- Square Test, and ultivariate test that is Logistic Regression. To calculate the income smoothing used Eckel indexs. The result of the univariate test showed that industrial sectors and profitability between companies's income smoothing practice and the other companies's income smoothing practice has significantly differences. The multivariate test with logistic regression give result that only profitability have significant influence to income smoothing practice.keywords : Income smoothing, size, profitability, operating leverage, and industrial sectors.